Microstructure and mechanical properties of spark plasma sintered SiC ceramics aided by B4C. Issue 8 (1st June 2020) - Li, Chenran; Li, Shuang; An, Di; Xie, Zhipeng
Abstract: Silicon carbide ceramics were densified by spark plasma sintering (SPS) using Silicon carbide (SiC) powders with the sintering aid Boron carbide (B4 C). Dense solid-phase sintered SiC ceramics were obtained by SPS with a holding time of 5 min at a temperature of 1800 °C, which is 350 °C lower than that required by conventional pressureless sintering (PS). The microstructure and mechanical properties of the ceramics was systematically investigated for different sintering temperatures. The sample relative density, flexural strength, hardness, elastic modulus and fracture toughness were determined to be 98.6%, 592 MPa, 28.3 GPa, 461 GPa and 3.6 MPa m 1/2, respectively. The spark plasma sintered specimens showed superior mechanical properties and finer grains compared to the pressurelessly sintered specimen. The densification kinetics for the spark plasma sintered SiC ceramics and the role of B4 C in the sintering process were discussed. Graphical abstract: Image 1